Threatening Public Trust: The Crimes of Counterfeiting and Circulating Counterfeit Currency - Sri Hasrina; Syawal Amirul Syah; Awaluddin Yasir; Indah Sari Palinrungi; Kristianto Riki (HORIZON PUBLIC LEGAL STUDIES, 2026)
The criminal offenses of currency counterfeiting and the circulation of counterfeit money constitute serious crimes that threaten the stability of the monetary system, cause financial losses to society, and undermine public confidence in currency as a lawful means of payment. Therefore, effective law enforcement through the proper application of criminal law is essential to combat such offenses. This study aims to analyze the application of criminal law to the offenses of currency counterfeiting and the circulation of counterfeit money, as well as to examine the legal reasoning adopted by the judges in Decision Number 135/Pid.B/2016/PN.Tsm. This research employs a normative legal research method using both the statute approach and case approach. The legal materials consist of primary, secondary, and tertiary legal sources, which were analyzed qualitatively. The findings indicate that the panel of judges applied Article 245 of the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana), concluding that the defendant had intentionally circulated counterfeit currency while knowingly recognizing it as counterfeit. However, the judges' legal reasoning did not comprehensively address the possible application of the doctrine of a continuing offense voortgezette handeling under Article 64 of the Indonesian Criminal Code. Furthermore, offenses relating to currency have been more specifically regulated under Law Number 7 of 2011 on Currency, which provides a more comprehensive legal framework for safeguarding the national monetary system and protecting the integrity of the Indonesian Rupiah. This study concludes that the judges' legal reasoning primarily focused on establishing the constituent elements of the offense without comprehensively examining the legal characterization of the series of acts committed by the defendants based on the facts established during the trial. Furthermore, in cases involving currency counterfeiting and the circulation of counterfeit money, judges should also take into account the broader objectives of sentencing, including social defence, crime deterrence, and the protection of the stability of the national monetary system. A more comprehensive judicial analysis of these aspects is essential to ensure legal certainty, consistency in the application of criminal law, and effective protection of the public interest.